The Contemporary Novel and the City Re-conceiving National and Narrative Form - Khanna, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book examines the deeply divided terrain of the twentieth century city and its formative impact on narrative fiction. It focuses on two major 'world authors' at the two ends of the twentieth century who write, systematically, about the colonial and postcolonial cities they were born in: James Joyce and Dublin, and Salman Rushdie and Bombay.